Answer:
(ab - 6)(2ab + 5)
Step-by-step explanation:
Assuming you require the expression factorised.
2a²b² - 7ab - 30
Consider the factors of the product of the coefficient of the a²b² term and the constant term which sum to give the coefficient of the ab- term
product = 2 × - 30 = - 60 and sum = - 7
The factors are - 12 and + 5
Use these factors to split the ab- term
= 2a²b² - 12ab + 5ab - 30 ( factor the first/second and third/fourth terms )
= 2ab(ab - 6) + 5(ab - 6) ← factor out (ab - 6) from each term
= (ab - 6)(2ab + 5) ← in factored form
Answer:
122*
122 degrees
Step-by-step explanation:
m∠GEF is 13 less than 5 times m∠DEG and m∠DEF = 149*
Solution:
As per given data,
m∠GEF = 5m∠DEG - 13* … (i)
m∠DEF = 149* -> m∠GEF + m∠DEG = 149* .. (ii)
Substituting value of m∠GEF in (ii)
We get,
(5m ∠DEG - 13*) + m∠DEG = 149*
6m ∠DEG - 13* = 149*
6m ∠DEG = 149* + 13* = 162*
m∠DEG = * = 27*
Substituting value of m∠DEG in (i)
We get,
m∠GEF = 5(27*) - 13*
m∠GEF = 135* - 13* = 122*
Answer:
I believe your rule would be (The rule is add 3)
Step-by-step explanation:
If you have -9 and you get to -6 that means you added an interval of 3
-9,-6,-3,0,3 is how it would continue
(The rule is add 3)
Are you sure you wrote all the correct numbers because it does not work